PEMBELAJARAN KALKULUS DIFERENSIAL MATERI FUNGSI IMPLISIT BERBANTUAN PEAR-DECK: PROFIL PROSES DAN HASIL - Eka Nurmala Sari Agustina (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2023)
Changes in conditions during the covid-19 pandemic made teachers take more initiative to create interactive learning even in online learning conditions. One platform that provides interactive conditions is Pear Deck. By utilizing the Pear Deck, the researcher aims to find out the Pear Deck-assisted learning process, and its impact on learning outcomes in differential calculus course material for implicit function derivatives. The research was applied to 18 second-semester mathematics education students with 15 students writing test subjects. The results showed that more than 80% of students were actively involved in lectures and were more active in conveying their opinions from the analysis of problem-solving procedures in this interactive learning. Research also shows that the results of implementing Pear Deck-assisted learning have a positive and significant effect as indicated by the value of t = 5.082 with a significance value of 0.0. The amount of this learning contribution to learning outcomes is 66.5%.